Application of Criminal Sanctions Against The Crime of Child Rape Linked with Article 82 of Act No. 35 of 2014 Concerning The Protection of Children - Ervin Faizal Nurdiansyah (Jurnal Daulat Hukum, 2018)
This study aimed to analyze the application of criminal sanctions against child rape. Legal issues that arise in this research include: How the application of criminal sanctions against criminal fines rape of children in the jurisdiction of Polresta Cirebon, and How the effectiveness of the application of criminal sanctions against perpetrators of child rape fines in Polresta Cirebon Jurisdiction. This research is a normative law and empirical legal research based on the consideration that in addition to leaving of the Act, the researchers also explored what is in the field related to the title of the researchers adopted, it can be concluded that the application of criminal sanctions penalties against perpetrators of criminal acts of rape of children Polresta Cirebon Jurisdiction in accordance with article 82, paragraph (1) and (2) of Act No. 35 of 2014 on Child Protection that the penalties are imprisonment of at least five (5) years and a maximum of 15 (fifteen) years and a maximum fine of Rp 5,000,000,000.00 (five billion rupiah). While the effectiveness of the application of criminal sanctions against child rape because the victim has not been effective enough that the injured party did not receive material compensation to pay for treatment and rehabilitation. For offenders, penalties are less able to provide a deterrent effect because the perpetrators are not able to pay these fines can be replaced with imprisonment for a long time very briefly. While the effectiveness of the application of criminal sanctions against child rape because the victim has not been effective enough that the injured party did not receive material compensation to pay for treatment and rehabilitation. For offenders, penalties are less able to provide a deterrent effect because the perpetrators are not able to pay these fines can be replaced with imprisonment for a long time very briefly. While the effectiveness of the application of criminal sanctions against child rape because the victim has not been effective enough that the injured party did not receive material compensation to pay for treatment and rehabilitation. For offenders, penalties are less able to provide a deterrent effect because the perpetrators are not able to pay these fines can be replaced with imprisonment for a long time very briefly.Keywords: Criminal sanctions; Child Rape; Child Protection.